Modelo de negócios : Yournews agregador de conteúdo e curadoria de mídias independentes - Pinto, Raul Galhardi (2019)
This work aims to create a business model based on independent media news curation, following the characteristic scope of a Professional Master's Degree. For this, this research seeks to trace the current panorama of the crisis of the journalistic business model, as a result of the fall in advertising revenues, and how this has impacted the global and Brazilian media ecosystem, with a special emphasis on the role of curators in this scenario. Based on the analysis of research and studies, which indicate that there is a search for vehicles with credibility and independence and an intention of the public to pay for these media contents, it is sought to define who is this target audience that already pays or is willing to pay for this news. Another stage of the project consists in performing case studies of content aggregation platforms. Finally, a business model is designed that seeks to propose a possible way out for the crisis of business models of the media, especially independente ones, through the creation of a news curation platform based on signatures and micropayments.